The Effect of Carbon Emission Disclosure on Company Value Using Corporate Governance as a Moderating Variable - Nona, Marietha Anggryani Dua; Putikadea, Insyirah (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the effect of carbon emission disclosure and profitability on firm value with corporate governance as a moderating variable. The research method used is quantitative method, with SPSS software, and data analysis techniques using multiple linear regression analysis, and Moderated Regression Analysis (MRA). This study uses a sample of holding companies involved in the energy sector, and listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The results show that carbon emission disclosure has a negative effect on firm value, and corporate governance is able to strengthen the relationship between carbon emission disclosure and firm value.